Three billboards outside Ebbing, Missouri [videorecording (DVD)] - McDonagh, Martin; McDormand, Frances; Harrelson, Woody; Rockwell, Sam (Twentieth Century Fox Home Entertainment, 2018)
After months have passed without a culprit in her daughter's murder case, Mildred Hayes makes a bold move, painting three signs leading into her town with a controversial message directed at William Willoughby, the town's revered chief of police. When his second-in-command Officer Dixon, an immature mother's boy with a penchant for violence, gets involved, the battle between Mildred and Ebbing's law enforcement is only exacerbated.